THE USE OF MARKETING STRATEGY IN THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Mamatkulova Shoira Jalolovna (Scholars Digest Publishing, 2023)
This article highlights ways to use marketing strategies in the development of small businesses and private enterprises.
Keywords: small business, entrepreneurship, marketing, innovation, strategy, competition.